The Role of Hadith in Learner Character Building: An Analysis of The Tradition of Muslim Family Education: Peran Hadis dalam Pembentukan Karakter Peserta Didik: Analisis pada Tradisi Pendidikan Keluarga Muslim - Samsul Hadi; Samsudin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Character development in education cannot be separated from the role of the family as the first and main environment in the process of internalizing good values. In the tradition of Islamic education, especially related to the Muslim family, the Ḥadīth becomes one of the main sources of shaping the moral and spiritual values of students. This study examines in depth the role of Ḥadīth in the formation of children’s character through the tradition of Muslim family education. Two questions become the starting point of the study: first, how is Ḥadīth conceptualized in the form of a character education framework; second, how is the implementation of Ḥadīth in overcoming the moral-spiritual crisis of each learner? Through a descriptive-analytical qualitative approach based on library research, data is obtained from observation and inventory of various literatures that speak about this matter. The results showed that the Ḥadīth is not only a normative foundation, but also used as a practical guide in shaping character such as honesty, responsibility, courtesy, and empathy. In fact, the prophet also consciously modeled the importance of good character which was reflected in the relationships that took place with the companions. In addition, the integration of Ḥadīth values in daily family routines has proven effective in building children’s moral awareness from an early age. In the end, this study confirms the importance of revitalizing the role of Ḥadīth in family-based character education to strengthen the moral foundation of the young Muslim generation in the modern era.